Diseño de un Banco de Ensayos por Transferencia de Calor por Tuberías para la Enseñanza en Ingeniería Mecánica Eléctrica - Silva, Carlos Alexis Alvarado; Montes, Carlos Alfredo Miñope; Rosado, Victor Orlando Gamarra [UNESP]; de Oliveira, Geraldo Cesar Rosario [UNESP] (My University, 2023)
This work presents a bank of heat transfer tests by pipelines from which experimental experiments are conducted by conduction and convection, and in this way, to analyze the results of this phenomenon of theoretical and experimental manner. Specifically, to evaluate the efficiency in the pipes, among which are a simple one, with fins and another with thermal insulation. Using different thermal insulators, one at a time and separate. In this set of tests the experimental results are recorded and verified by a thermographic chamber, instrumentation commonly used in the academic field of engineering branches that teaches topics related to the science of heat transfer, which illustrates in a didactic way difficult problems to visualize, solve It is always impossible to discover these physical phenomena exactly.
Design of a bench of tests for heat transfer by pipes for teaching in Electrical Mechanical Engineering
Keywords: Conduction; convection; Heat transfer; Test bench by pipes